Integrative omics analysis of p53‐dependent regulation of metabolism. Issue 3 (23rd January 2018) - Huang, Jiajun; Long, Ze; Lin, Wanjun; Liao, Xiaolin; Xie, Ying; Liu, Liang; Ma, Wenzhe
Abstract : Accumulated evidence in the last decade implies that regulation of metabolism by p53 represents a reviving mechanism vital to prevent tumorigenesis. To gain a more in‐depth understanding of metabolic regulation by baseline levels of p53, we employed both metabolomics and transcriptomics analysis with human colon cancer cell‐line HCT116 depleted of p53. Metabolomics analyses with UPLC/quadrupole time‐of‐flight mass spectrometry identified 283 significantly changed metabolites including 138 important metabolites. Transcriptomics analysis with microarray revealed 1317 differentially expressed genes. By integrated analysis of both omics data, we found nucleotides metabolism and sulfur‐related metabolism are of great importance. Our study provided a pilot comprehensive view of the metabolism regulated by p53 and suggests several potential p53 targets in metabolism for further study. Abstract :